A closer look on the polyhydroxybutyrate- (PHB-) negative phenotype of Ralstonia eutropha PHB-4. - Matthias Raberg; Birgit Voigt; Michael Hecker; Alexander Steinbüchel (PLoS ONE, 2014)
The undefined poly(3-hydroxybutyrate)- (PHB-) negative mutant R. eutropha PHB-4 was generated in 1970 by 1-nitroso-3-nitro-1-methylguanidine (NMG) treatment. Although being scientific relevant, its genotype remained unknown since its isolation except a recent first investigation. In this study, the mutation causing the PHA-negative phenotype of R. eutropha PHB-4 was confirmed independently: sequence analysis of the phaCAB operon identified a G320A mutation in phaC yielding a stop codon, leading to a massively truncated PhaC protein of 106 amino acids (AS) in R. eutropha PHB-4 instead of 589 AS in the wild type. No other mutations were observed within the phaCAB operon. As further mutations probably occurred in the genome of mutant PHB-4 potentially causing secondary effects on the cells' metabolism, the main focus of the study was to perform a 2D PAGE-based proteome analysis in order to identify differences in the proteomes of the wild type and mutant PHB-4. A total of 20 differentially expressed proteins were identified which provide valuable insights in the metabolomic changes of mutant PHB-4. Besides excretion of pyruvate, mutant PHB-4 encounters the accumulation of intermediates such as pyruvate and acetyl-CoA by enhanced expression of the observed protein species: (i) ThiJ supports biosynthesis of cofactor TPP and thereby reinforces the 2-oxoacid dehydrogenase complexes as PDHC, ADHC and OGDHC in order to convert pyruvate at a higher rate and the (ii) 3-isopropylmalate dehydrogenase LeuB3 apparently directs pyruvate to synthesis of several amino acids. Different (iii) acylCoA-transferases enable transfer reactions between organic acid intermediates, and (iv) citrate lyase CitE4 regenerates oxaloacetate from citrate for conversion with acetyl-CoA in the TCC in an anaplerotic reaction. Substantial amounts of reduction equivalents generated in the TCC are countered by (v) synthesis of more ubiquinones due to enhanced synthesis of MenG2 and MenG3, thereby improving the respiratory chain which accepts electrons from NADH and succinate.